Prognostic significance of magnetic resonance imaging of bone marrow in previously untreated patients with multiple myeloma - Moulopoulos, L.A.; Gika, D.; Anagnostopoulos, A.; Delasalle, K.; Weber, D.; Alexanian, R.; Dimopoulos, M.A. (Annals of Oncology, 2005)
Background: Magnetic resonance imaging (MRI) has been a useful technique for the assessment of patients with multiple myeloma (MM). We evaluated the prognostic significance of different MRI patterns in symptomatic patients with MM. Patients and methods: A total of 142 symptomatic MM patients underwent MRI before treatment. MRI patterns of involvement were correlated with known prognostic variables, including the International Staging System (ISS), response to treatment and survival. Results: Focal marrow lesions were identified in 50% of patients, diffuse marrow replacement in 28%, a variegated pattern in 14% and normal pattern in 8%. When patients with the diffuse pattern were compared with patients with the other MRI patterns, they had features of more advanced disease such as higher ISS, anemia, hypercalcemia, elevated lactate dehydrogenase and extensive marrow plasmacytosis. Response rate was similar among patients with different MRI patterns. Median survival was 24 months for patients with the diffuse pattern, 51 months for those with the focal pattern, 52 months for those with the variegated pattern and 56 months for patients with the normal pattern (P = 0.001). The presence or absence of a diffuse MRI pattern separated patients with ISS stages I and II into two subgroups with significantly different survival times of 28 months and 61 months, respectively (P = 0.01). Furthermore, a diffuse MRI pattern predicted inferior outcome regardless of whether or not patients had received high-dose therapy with autologous stem cell transplantation. Conclusion: Diffuse marrow replacement on MRI adds to the evaluation of patients with multiple myeloma and their management. © 2005 European Society for Medical Oncology.
Keywords: MRI; multiple myeloma; Prognosis